Hubungan Pemberian ASI Eksklusif dengan Kejadian Diare pada Bayi Usia 0–6 Bulan - Praditanaya, Gede; hendra, Dr. dr. Komang Hendra Setiawan, S.Ked., M.Kes.; pasek, dr. Made Suadnyani Pasek, S.Ked., M.Kes., M.Biomed., Sp.A. (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
Diarrhea is one of the leading causes of morbidity and mortality in children under five, especially in developing countries, including Indonesia. Exclusive breastfeeding for the first six months of life, as recommended by WHO, is believed to provide optimal protection against infectious diseases, including diarrhea, through its nutritional content and antibodies. This literature review focuses on scientific evidence in Indonesia regarding the relationship between exclusive breastfeeding and the incidence of diarrhea in infants aged 0–6 months, with particular attention to confounding factors such as sanitation conditions and maternal hygiene behaviors that have not been widely explored in previous studies. This review synthesizes findings from 10 relevant studies, consisting of 9 cross-sectional studies and 1 national data analysis. A total of six studies reported a significant association, with odds ratios ranging from 2.0 to 2.5, indicating that infants who were not exclusively breastfed had twice the risk of diarrhea compared to those who were exclusively breastfed. Overall, the evidence supports the promotion of exclusive breastfeeding integrated with environmental health interventions to reduce the burden of diarrheal disease in infants.